Fake News: uma abordagem em face da liberdade de expressão, internet e democracia - Horbach, Lenon Oliveira (Universidade do Vale do Rio dos Sinos, 2019)
This research aims to analyze the Fake News phenomenon regarding the fundamental right of freedom of expression, the resourcefulness in the internet network, as well as due to the democratic system, verifying the appropriateness of controlling the dissemination of false reports that cause disinformation of the whole society. This research has as problem the understanding of what elements justify the need for policies to avoid or restrain Fake News in the internet network and, also how to develop these policies without limiting fundamental rights while preserving the democratic system. For this research, the deductive method of approach was applied. This method is more suitable, since it had as starting point an international juridical-constitutional perspective and, then, apply the expertise in concrete cases in which the relation of Fake News and freedom of expression, internet and democracy is recognized. The investigative analysis will be developed from indirect documentation in primary sources, such as national, international and foreign legislation, judicial precedents, statistics and documents in general, as well as in secondary bibliographic sources, in particular, in books, scientific periodicals, and in the internet network etc. Through this study, it has been shown that freedom of expression - no matter it is a fundamental right that allows free and public expression within a community, enabling political, social and economic articulation - is suffering more and more limitations, along with a phenomenon of Post-truth, which calls into question all the scientific certainties built up over the last centuries in the world. Currently, the legislation and policies of the executive branch seek to regulate Fake News on the Internet. These policies are based on the comparative law of other countries, but they find obstacles to legal, philosophical and social problems. In addition, before the regulation of Fake News in the internet it is necessary to observe the Web as an integral space, knowing both the visible and the invisible part. However, the theory of the technological imaginary is glimpsed, highlighting the object phenomenon, as well as the premise that every technology, when received by a community, causes feelings of fear, expectation and doubt, modifying the internal culture of that society. Finally, the so-called personification of content in a coordinated way, which occurs through algorithms of social platforms, placing the user within a social bubble, causes direct interference in the freedom of the citizen, reaching one of the keys of democracy in the way described by Bobbio, fomenting possible illegitimacy of the democratic system.
Keywords: Fake news; Liberdade de expressão; Democracia; Internet; Fake news; Freedom of expression; Democracy; Internet; ACCNPQ::Ciências Sociais Aplicadas::Direito